Considerations on State Pension Age in the United Kingdom. (26th May 2015) - Hammond, R.; Baxter, S.; Bramley, R.; Kakkad, A.; Mehta, S.; Sadler, M.
Abstract: State Pension Age (SPA) is an issue of topical interest in the United Kingdom at the time of writing owing to the Government's plans to link SPA at future dates to estimates of the projected longevity of the population. This paper considers the background to the current position, how the linkage is proposed to work, other factors that may need to be considered and some changes in the proposed State pension regime that could be alternatives to, or complementary with, a changing SPA.